Experiencing term-time employment as a non-traditional aged university student: a Welsh study. Issue 3 (2nd July 2016) - Mercer, Jenny; Clay, James; Etheridge, Leanne
Abstract: Engaging in term-time employment appears to be becoming a common feature of contemporary UK student life. This study examined the ways in which a cohort of full-time non-traditional aged students negotiated paid employment whilst pursuing a full-time higher education course in Wales. Taking a qualitative approach to explore this further, semi-structured interviews were conducted with 14 non-traditional age students, and analysed using thematic analysis. Findings indicated that participants felt compromises had to be made in both academic and social spheres in order to accommodate conflicting time demands; there was a desire to maintain the quality of life experienced before entering university; and the impact of working and studying presented challenges for both their academic engagement and personal relationships. These findings will be discussed in relation to the extant literature, and debate around how higher educational institutions may seek to address and acknowledge these issues is considered.